Two nematode species from freshwater and marine fishes in Thailand, including Ascarophis scatophagi sp. nov. (Cystidicolidae) from Scatophagus argus (Scatophagidae) - Moravec, František; Yooyen, Thanapon; Sanprick, Amornrat (Acta Parasitologica, 2018)
One new and one known species of parasitic nematodes are reported from Thailand for the first time: Falcaustra kaverii (Karve et Naik,1951) (Kathlaniidae) from the intestine of the freshwater fish Poropuntius deauratus (Valenciennes) (Cyprinidae) (new host record) and Ascarophis scatophagi sp. nov. (Cystidicolidae) from the intestine of the marine fish Scatophagus argus (Linnaeus) (Scatophagidae). The morphology of both these species was studied with the use of light (LM) and scanning electron microscopy (SEM) (the latter method used for F. kaverii for the first time). The new species (A. scatophagi) is mainly characterized by nonfilamented, markedly elongate-oval eggs (size 42-45 × 18 μm), spicules 555-642 μm and 105-150 μm long, the muscular/glandular oesophagus length ratio (1:13-34), bifurcate deirids, the length of the female tail (159-249 μm) and cephalic structures typical of the nominotypical subgenus Ascarophis. Representatives of Falcaustra Lane, 1915 and Ascarophis van Beneden, 1871 were not previously reported from fishes in Thai waters.
Keywords: Thajsko; biometrie; Animals; Thailand; Microscopy, Electron, Scanning; Ascaridida Infections; Ascaridida; Spiruroidea; nemoci ryb; mikroskopie elektronová rastrovací; anatomické struktury zvířat; infekce hlísticemi řádu Ascaridida; infekce hlísticemi řádu Spirurida; Fish Diseases; Fishes; ryby; Animal Structures; Biometry; Spirurida Infections; zvířata; mikroskopie; Microscopy